Effect of Fast Pyrolysis Operation Condition on Bio-Oil Production of Red Meranti Sawdust - Nor Wahidatul, Azura; Zularisam, A. W.; Mimi Sakinah, A. M.; Mohd, Nasrullah; Siti, Norsita (2017)
Fast pyrolysis of red meranti sawdust was carried out in a bench-scale tabular furnace reactor for bio-oil production. In this work, the effect of pyrolysis temperature, N2 gas flow rate, retention time and feed particle size were studied. Results showed that the bio-oil achieved maximum yield about 63.2 wt. % at the temperature of 450 °C, N2 flow rate of 25 L/min and retention time for feed particle size of 0.3 mm was 60 min. From analysis, it can be concluded that the temperature was the most influential parameter upon bio-oil yield, followed by N2 sweeping gas flow rate into the reactor and retention time of biomass in furnace. Feed particles size was insignificantly effect bio-oil yield.